The effect of design education on creative design cognition of high school students. Issue 4 (2nd October 2019) - Gero, John; Yu, Rongrong; Wells, John
ABSTRACT: This paper presents results from a study exploring the relationship between design education and creative design cognition in high school students. Data from coded protocols of high school students with and without design education serve as the source. Audio/video recordings of student pairs engaged in a design task captured both their design approach and their concurrent design conversation. Following a verbal protocol methodology, videos were coded using the Function-Behaviour-Structure ontology coding scheme. This coding scheme was augmented by two further codes 'new' and 'surprising' as the basis for measuring design creativity. Results revealed significant differences between the two cohorts in creative design cognition, while no significant differences in general design cognition were found.